Efektivitas Ekstrak Etanol Kulit Biji Kacang Hijau (Vigna radiata L.) Sebagai Penumbuh Rambut Pada Kelinci Jantan New Zealand White - Azizah, Indah Wafiq; Pratama, Kharisma Jayak; Septiarini, Anita Dwi (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Hair has both psychological and social importance. Hair loss occurs physiologically and pathologically, such as hormones, lack of nutrients, exposure to free radicals, stress and genetic factors. Mung bean seed coat is rich in macronutrients and micronutrients such as protein, flavonoids and antioxidants. The purpose of this study is to determine the effectiveness of mung bean seed coat in increasing hair growth, as well as determining the optimal dose and time. This study used a pure experimental method with 3 New Zealand White rabbit test animals with 8 test groups. Neutral (without treatment), positive control (minoxidil 2%), negative control (aquadest) and 5%, 10%, 15%, 20% and 25% extract concentrations test groups. The results showed that mung bean seed coat extract (Vigna radiata (L.)) at a concentration of 20% with hair length which is 1,42 cm and hair weight of 0,943 grams and hair growth area of 3,41 cm2 compared to minoxidil 2% with hair leght for 14 days, which is 1,73 cm and 15th day hair weight of 1,240 grams and hair growth area for 14 days of 3 cm2.